UDVIKLING AF KOMPETENCER I EN BEHANDLINGSMÆSSIG SAMMENHÆNG: – et oplæg - Mathiassen, Charlotte (Psyke & Logos, 2022)
Within the context of competence development as the primary goal of treatment it is claimed that this project has to be subordinated the subjects ’life-project’. Furthermore it is claimed that during the course of treatment it may be necessary for the treatment it self to become its own goal, for a time replacing change in the life-activity of the subject as the primary goal of treatment. The author documents these points through a thorough presentation and description of three women’s life during and after a period of treatment in an institutional context. The basis of the documentation are the women’s own perspective on their life- and developmental projects.